The design and development of an experience measure for a peer community moderated forum in a digital mental health service - Mindel, Charlotte; Mainstone-Cotton, Lily; de Ossorno Garcia, Santiago; Sefi, Aaron; Sugarman, Georgia; Salhi, Louisa; Brick, Holly; Jackson, Katherine; Hanley, Terry (Frontiers in Digital Health, 2022)
Online digital mental health communities can contribute to users’ mental health positively and negatively. Yet the measurement of experience, outcomes and impact mechanisms relating to digital mental health communities is difficult to capture. In this paper we demonstrate the development of an online experience measure for a specific children and young people’s community forum inside a digital mental health service. The development of the Peer Online Community Experience Measure (POCEM) is informed by a multi-phased design: (i) item reduction through Estimate-Talk-Estimate modified Delphi methods, (ii) user testing with think-aloud protocols and (iii) a pilot study within the digital service community to explore observational data within the platform. Experts in the field were consulted to help reduce the items in the pool and to check their theoretical coherence. User testing workshops helped to inform the usability appearance, wording, and purpose of the measure. Finally, the pilot results highlight completion rates, differences in scores for age and roles and ‘relate to others’, as the most frequent domain mechanism of support for this community. Outcomes frequently selected show the importance of certain aspects of the community, such as safety, connection, and non-judgment previously highlighted in the literature. Experience measures like this one could be used as indicators of active therapeutic engagement within the forum community and its content but further research is required to ascertain its acceptability and validity. Multi-phased approaches involving stakeholders and user-centred design activities enhances the development of digitally enabled measurement tools.